Origin and Dispersal of Domesticated Peach Palm - Clement, Charles R.; Cristo-Araújo, Michelly de; Coppens d'Eeckenbrugge, Geo; Reis, Vanessa Maciel dos; Lehnebach, Romain; Picanço-Rodrigues, Doriane (Frontiers in Ecology and Evolution, 2017)
Peach palm (Bactris gasipaes Kunth) is the a Neotropical palm domesticated by Native Americans. Its domestication resulted in a set of landraces (var. gasipaes), some with very starchy fruit used for fermentation, others with an equilibrium of starch and oil used as snacks. Which of the three wild types (var. chichagui) was involved and where the domestication process began are unclear, with three hypotheses under discussion: an origin in southwestern Amazonia; or in northwestern South America; or multiple origins. We reevaluate one of the wild types, defining it as the incipient domesticate, and then evaluate these hypotheses using the Brazilian peach palm Core Collection and selected herbaria samples to: 1) model the potential distributions of wild and domesticated populations; 2) identify the probable origin of domestication with a phylogeographic analysis of chloroplast DNA sequences; and 3) determine the dispersal routes after domestication using spatial analysis of genetic diversity based on 17 nuclear microsatellite loci. The two very small-fruited wild types have distinct distributions in the northern Andes region and across southern Amazonia, both under moderately humid climates, while the incipient domesticate, partly sympatric with the southern wild type, is also found along the Equatorial Andes, in a more humid climatic envelope, more similar to that of the domesticated landraces. Two distribution models for Last Glacial Maximum conditions (CCSM4, MIROC) also suggest distinct distributions for the two wild populations. The chloroplast DNA phylogeographic network confirms the area of sympatry of the incipient domesticate and the southern wild type in southwestern Amazonia as the origin of domestication. The spatial patterns of genetic diversity confirm the proposal of two dispersals, one along the Ucayali River, into western Amazonia, northwestern South America and finally Central America; the other along the Madeira River into central and then eastern Amazonia. The first dispersal resulted in very starchy fruit for fermentation, while the second may have been later and resulted in snack fruits. Further explorations of southwestern Amazonia are essential for more precise identification of the earliest events, both with new archaeological methods and genetic analyses with larger samples.